2014
DOI: 10.1115/1.4025618
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Viscoplastic Model for High Temperature Low Cycle Fatigue of Service-Aged P91 Steel

Abstract: The finite element (FE) implementation of a hyperbolic sine unified cyclic viscoplasticity model is presented. The hyperbolic sine flow rule facilitates the identification of strain-rate independent material parameters for high temperature applications. This is important for the thermo-mechanical fatigue of power plant where a significant stress range is experienced during operational cycles and at stress concentration features, such as welds and branch connections. The material model is successfully applied t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Sauzay and co-workers [15,16] have established that this effect is primarily related to the loss of the lath microstructure and a concomitant reduction in dislocation density. Barrett et al [17,18] showed that a significant strain-rate effect occurs for P91 at 600 °C, although the effect is negligible for temperatures of 500 °C and less. This strain-rate effect has also been observed in other 9Cr martensiticferritic steels, such as P92 [11] and MarBN [19], at temperatures in excess of 550 °C.…”
mentioning
confidence: 99%
“…Sauzay and co-workers [15,16] have established that this effect is primarily related to the loss of the lath microstructure and a concomitant reduction in dislocation density. Barrett et al [17,18] showed that a significant strain-rate effect occurs for P91 at 600 °C, although the effect is negligible for temperatures of 500 °C and less. This strain-rate effect has also been observed in other 9Cr martensiticferritic steels, such as P92 [11] and MarBN [19], at temperatures in excess of 550 °C.…”
mentioning
confidence: 99%
“…The constitutive behaviour of the material is defined using a unified cyclic viscoplastic material model with combined non‐linear isotropic and kinematic hardening, as described in more detail by Barrett et al This model has been implemented in an implicit UMAT subroutine in the commercial finite element code Abaqus and modified in this work to include life prediction and fatigue damage effects. A flowchart of the constitutive damage model is presented in Figure .…”
Section: Methodsmentioning
confidence: 99%
“…More details on these experimental tests are provided in [52]. Data from a typical room temperature tensile test are shown in figure 5, taken from the same header [53] as the miniature three point bend specimen. The material model used within the continuum level FE analysis is also shown in the figure.…”
Section: Specimen Level Modellingmentioning
confidence: 99%